2012
DOI: 10.1111/j.1551-2916.2012.05451.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase Evolution upon Aging of Air‐Plasma Sprayedt′‐Zirconia Coatings: I—Synchrotron X‐Ray Diffraction

Abstract: Phase evolution accompanying the isothermal aging of free‐standing air‐plasma sprayed (APS) 7–8 wt% yttria‐stabilized zirconia (8YSZ) thermal barrier coatings (TBCs) is described. Aging was carried out at temperatures ranging from 982°C to 1482°C in air. The high‐temperature kinetics of the phase evolution from the metastable t′ phase into a mixture of transformable Y‐rich (cubic) and Y‐lean (tetragonal) phases are documented through ambient temperature X‐ray diffraction (XRD) characterization. A Hollomon–Jaff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 53 publications
4
84
1
2
Order By: Relevance
“…Simultaneous presence of two tetragonal phases along with cubic precipitates in YSZ, observed by room temperature XRD, in initially t zirconia has been reported in the literature. 25,26 Recent understanding of the precipitation of cubic phase in YSZ indicates that the tetragonal phase with large tetragonality is an artifact of the tetragonal phase being strained in the vicinity of the cubic precipitates due to coherency. 8 The present results are consistent with this hypothesis.…”
Section: Annealing Time (H)mentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneous presence of two tetragonal phases along with cubic precipitates in YSZ, observed by room temperature XRD, in initially t zirconia has been reported in the literature. 25,26 Recent understanding of the precipitation of cubic phase in YSZ indicates that the tetragonal phase with large tetragonality is an artifact of the tetragonal phase being strained in the vicinity of the cubic precipitates due to coherency. 8 The present results are consistent with this hypothesis.…”
Section: Annealing Time (H)mentioning
confidence: 99%
“…The presence of two tetragonal phases during annealing of YSZ at temperatures above 1100 • C has previously been reported. 9,[22][23][24] The outermost peaks are ascribed to the tetragonal phase with the largest c/a ratio in the phase assembly, designated as t 1 . The next inner set of peaks is ascribed to a tetragonal phase with smaller c/a ratio, designated as t 2 .…”
Section: Annealing Time (H)mentioning
confidence: 99%
“…6, and is visually much clearer to see in the Kα 2− stripped data than in the raw data containing both Kα 1 and Kα 2 contributions as used for the fitting. This looks similar to the peaks seen in the monochromatic synchrotron XRD data presented by Lipkin [30] whereby up to 3 tetragonal phases (t, t′, t″) were fitted to the peak grouping at 74°. Following this work, simple peak profile fitting without a structural model showed that 4 peaks fitted better than 3, and based on the fitted peak positions at 74°an extra t″ phase of lowtetragonality c/a = 1.006 could be defined and the lattice parameters determined.…”
Section: Whole Powder Pattern Fitting (Wppf)mentioning
confidence: 88%
“…Essentially a continuum of increasingly tetragonal phases can be formed by gradual distortions of the parent cubic lattice along the c-direction which are displacive, not diffusive. Evidence of this includes massive twinning seen in grains following the c → t′ transformation [30].…”
Section: Introductionmentioning
confidence: 97%
“…[41] The decomposition of the t¢ phase at high temperatures limits the maximum operating temperature of the coating. [91][92][93] In addition to changes in the ceramic thermal barrier coating, changes in the other coatings in the thermal barrier system can occur, so the lifetime of the coating depends on the compositions and geometries of all system components. [35] Thus, models for predicting thermal barrier coating lifetimes need to include factors such as growth of the thermally grown oxide (TGO) on the alloy and sintering of the ceramic thermal barrier coating.…”
Section: Stabilitymentioning
confidence: 99%